Kilka uwag w związku z kolonią Flawiopolis na Chersonezie Trackim (Plin. HN 4, 47) - Jurkowski, Marek (Studia Europaea Gnesnensia, 2023)
The article examines the validity of the view which challenges Pliny the Elder’s information concerning the existence of the colony of Flaviopolis on the Thracian Chersonesus, arguing that its name was unusual for a colony. The author discusses situations in which the title of the colony could have been combined with local place names ending in -polis. Furthermore, attention is drawn to the peculiar character of Natural History as a source for toponomastic research and the fact that the latter work also mentions the colony of Flaviobrica, whose name seems interesting given the doubts surrounding the legal status of the Thracian Flaviopolis.